Effects of global warming on Eurasian perch (Perca fluviatilis) in the Baltic Sea : does the growth response to increased temperatures differ along a latitudinal gradient? - Grunander, Mattias (SLU/Dept. Of Aquatic Resources, 2018)
Anthropogenically caused climate change, i.e. global warming, is anticipated to affect all living organisms. Particularly ectotherms are predicted to show strong responses to the increased warming, as their body temperature closely tracks ambient temperatures and because body temperature profoundly affects many physiological functions e.g. locomotion, fecundity, metabolism and growth. This study attempts to answer whether increasing temperature has affected the growth rate and body length at age in Baltic Sea perch, and if the effect of increasing temperatures varies depending on latitude. It was carried out through analyses of temporal trends in size-specific growth at different ages (growth years), size-specific growth rates estimated from the whole life-span, as well as length at age one in perch from three areas in the southern (Kvädöfjärden), central (Finbo) and northern (Holmön) Baltic Sea, and by analysing whether variation in temperature explained the observed changes over time. Positive relationships were found between body length at age one and temperature in all areas. Size-specific growth rate at age increased significantly with temperature, for all ages and locations, except for six-year old perch in Holmön. All size classes of Finbo and the 145 mm class of Holmön and Kvädöfjärden demonstrated positive relationship of the size-specific life-span integrated growth rate with increasing temperatures, but the smallest and largest size classes in those two areas did not. Of the three areas investigated, my results suggest that the responses in body length at age one and size-specific growth rate for growth year one and two to increased temperature were comparatively stronger in the north than in the central and south Baltic Sea. For the size-specific growth of older individuals or in the size class 145 mm, no such latitudinal pattern emerged. Overall, adjusted r2 values were low, indicating that temperature does not explain the variation in growth rate well for any of the models. Still, the significant relationships to temperature indicate that warming could have contributed to increased perch growth rate and temperature, and that the response in growth for individuals younger than three years old, has been strongest in the north. This knowledge may be useful when making predictions on how an additional increase in temperature may affect the growth, and body length of perch. It may also help to generate a broader understanding of how the perch growth response changes to increasing temperature, given different latitudinal distributions.